2020
DOI: 10.1089/met.2019.0043
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Uric Acid with Metabolic Syndrome and Its Components: A Cross-Sectional Study in Chinese Coastal Population

Abstract: Objective: Few studies reported the association between serum uric acid and the prevalence of metabolic syndrome in China's coastal residents. We aimed to examine the association between serum uric acid and the prevalence of metabolic syndrome as well as its components in adults and elderly from Shenzhen (a China's coastal city). Methods: We conducted a survey in a community-based household population in Shenzhen, collecting data about 4049 participants aged 20-69 years. Based on the data, we determined the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Interestingly, serum uric acid concentration decreased significantly after weight reduction only in the MR group. Besides dietary risk factors such as consumption of animal-derived purine-rich foods, legumes, and alcoholic beverages [ 31 , 32 , 33 ], serum uric acid concentration is known to be associated with metabolic syndrome [ 34 , 35 ]. Many studies have shown that serum uric acid is also associated with the risk for developing NAFLD [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, serum uric acid concentration decreased significantly after weight reduction only in the MR group. Besides dietary risk factors such as consumption of animal-derived purine-rich foods, legumes, and alcoholic beverages [ 31 , 32 , 33 ], serum uric acid concentration is known to be associated with metabolic syndrome [ 34 , 35 ]. Many studies have shown that serum uric acid is also associated with the risk for developing NAFLD [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Recent studies found that an increase in serum UA levels was closely related to the occurrence of metabolic syndromes other than gout, such as dyslipidaemia, abnormal glucose tolerance, hypertension, central obesity and other metabolic disorders. 16 UA also induces insulin resistance via endothelial cell mitochondrial oxidative stress. 17 The relationship between UA and IGF-1 has received some attention, but there is little research on this relationship.…”
mentioning
confidence: 99%
“…SERUM URIC ACID (SUA) levels are positively associated with multiple metabolic abnormalities including obesity, hypertension, hyperglycemia, and hyperlipidemia [1]. Elevated SUA levels are independently correlated with the incidences of hypertension and metabolic syndrome (MetS) in some Asian countries including China, Japan, and Korea [2][3][4][5]. For patients with type 2 diabetes mellitus (T2DM), higher SUA levels are associated with the lower estimated glomerular filtration rate (eGFR) and higher prevalence of diabetic nephropathy, but not diabetic retinopathy [6].…”
mentioning
confidence: 99%